HUBUNGAN ATTACHMENT (KELEKATAN) ORANG TUA DENGAN RESIKO PERILAKU KEKERASAN REMAJA - Cindy Sukma Pertiwi Djais; Jumaini " "; Gamya Tri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractAdolescents is a period that is associated with the achievement of self-identity, if they are fail to reach a positive identity it will cause aberrant behavior in teeneger as violent behavior. This study aims to determine the relationship between parents attachment with adolescents at risk of violent behavior at SMA PGRI Pekanbaru. This research used descriptive research correlation design and cross sectional approach. The sample were 121 respondents. They are taken based on inclusion criteria by used proportionate stratified random sampling technique. Measuring instrument used questionnaire IPPA-R (Inventory Parents and peer attachment-Revised) for variable parents attachment who have been translated and tested for validity and reliability by Binarti (2012) and a questionnaire Agrresion Buss and Perry for the variable risk of violence behavior that has been translated and tested for validity and reliability by Niken (2012). The analysis which is used was univariate analysis to determine the distribution frequency and bivariate analysis using chi-square test to relations independent variabel and dependent variabel. Results of statistical test Chi-Square indicates that the P value = 0.649 > a = (0.05), so in this research there is no significant relationship between parents attachment with violent behavior risk of adolescents. The results of this study are expected to be a concern for parents to establish two-way communication, mutual trust and do not make an alienation with teenagers. Concern for the school to be able to make a policy or regulation regarding the violent behavior of teenagers. Keywords: Adolescent, attachment, IPPA-R, violent behavior